Origin of atmospheric Cl-, Br- and I -containing impurities in the glacier of Galindez Island, Vernadsky - Bogillo, V.; Borhers, R.; Bazylevska, M. S. (Ukrainian Antarctic Journal, 2005)
The volatile halocarbons play a key role in depletion of stratospheric ozone layer, in change of oxidative potential of troposphere and in atmospheric radiation balance. However, the relative contributions of their fluxes from anthropogenic and such natural sources, as lithosphere, soils, terrestrial plants, oceanic biota, biomass burning, abiotic photo- and redox-reactions of natural organic matter in presence of halide ions are not known enough. The possible sources have been discussed for volatile Cl, Br- and I-containing halocarbons identified in high concentrations in young and aged layers of retreated glacier on Galindez Island, Argentine Islands Archipelago, Western coastal Antarctica and the formation mechanisms have been proposed here. Their atmospheric mixing ratio in the ice samples has been compared with the results for air analysis in deep cores of firn from Central Antarctica, Central Greenland and Canadian Arctic, and with their content in air over Southern Ocean and in the water. It was shown that CH2Br2 and CHBr3 can be formed from ice microalgaes deposited on the snow surface and from coastal macroalgaes wind-blown on the surface through the mechanism of haloform reaction and/or sulfo- haloform rearrangement. Similar sources are possible for mono-halocarbons (CH3Cl, C2H5Cl, CH2=CHCl, CH3Br, CH3I, CH2=CHI and C2H5I), which found in high concentrations in the ice samples. The alkylation of the halide ions by sulphur-containing bioorganic compounds or reaction of chloroperoxidase with organic compounds containing CH group activated by carbonyl group in presence of hydrogen peroxide and halide ions can be main mechanisms for biogenic formation of the halocarbons. Furthermore, they may be formed in consequence of such abiotic reactions as photolysis of organic matter generated from the deceased algae on the snow surface in presence of halide ions in accordance with mechanism of Norrish II type reaction (photodissociation of α-carbonyls) and/or oxidation-reduction reaction of the matter with Fe3+ ions and halide ions in more deep layers of snow and firn of the glacier. The possible concentrations of the ions and the compounds in Antarctic snow were obtained and the rates of these processes were compared. It was found that photolysis of the organic matter is more effective in comparison with the redox-reaction of the matter. The temporal variations of CH3Cl, C2H5Cl, CH3Br, CH3I and C2H5I along the glacier profile were analyzed and compared with those obtained for CO2 and COS. It was found that hydrolysis processes of CH3Br and CH3I in quasi-liquid water films on the snow and firn surface as well as in the infiltrated water have a great impact on the temporal variations for these compounds whereas the effect of nucleophilic substitution reactions of Cl- ion in these species can be neglected.